The Krüppel-like factor 6 represses proliferation and invasion of cutaneous malignant melanoma - Li, Yuan-Yuan; Zheng, Qi-Ming; Zhang, Nan; Zhang, Min (Polish Journal of Pathology, 2023)
Cutaneous carcinoma is one of the most common neoplasm tumors in the West. Its incidence rate is one of the fastest growing tumors in China. The Krüppel-like factor 6 (KLF6) is a latent tumor suppressor. Decreased KLF6 is related to the occurrence and progression of many cancers in human. Our previous studies have demonstrated that KLF6 was down-regulation in cutaneous malignant melanoma (CMM), and was significant correlated with ulcer, lymph node metastasis and clinical stage, suggesting that KLF6 loss is expected to become a biological indicator of poor prognosis in CMM patients. In this research, we would further study the features of KLF6 in the malignant progression of CMM. The expression of KLF6 was up-regulated by lentivirus infection containing KLF6, and short hairpin RNA (shRNA) was used for knockdown of KLF6 in CMM cells. Western blot, RT-qpcr, CCK8 assay, transwell migration assays, wound healing assay and flow cytometry were used to test the role of KLF6 in the CMM. We found that reduced expression of KLF6 significantly enhanced proliferation, migration and invasion. Moreover, KLF6 induced CMM cell apoptosis and G1 cycle arrest. The decreased KLF6 expression is expected to be a biological indicator of poor prognosis in CMM patients.